PAINT‐ing Fluorenylmethoxycarbonyl (Fmoc)‐Diphenylalanine Hydrogels. Issue 44 (18th June 2020) - Fuentes, Edgar; Boháčová, Kamila; Fuentes‐Caparrós, Ana M.; Schweins, Ralf; Draper, Emily R.; Adams, Dave J.; Pujals, Silvia; Albertazzi, Lorenzo
Abstract: Self‐assembly of fluorenylmethoxycarbonyl‐protected diphenylalanine (FmocFF) in water is widely known to produce hydrogels. Typically, confocal microscopy is used to visualize such hydrogels under wet conditions, that is, without freezing or drying. However, key aspects of hydrogels like fiber diameter, network morphology and mesh size are sub‐diffraction limited features and cannot be visualized effectively using this approach. In this work, we show that it is possible to image FmocFF hydrogels by Points Accumulation for Imaging in Nanoscale Topography (PAINT) in native conditions and without direct gel labelling. We demonstrate that the fiber network can be visualized with improved resolution (≈50 nm) both in 2D and 3D. Quantitative information is extracted such as mesh size and fiber diameter. This method can complement the existing characterization tools for hydrogels and provide useful information supporting the design of new materials. Abstract : Key aspects of hydrogels like fiber diameter, network morphology and mesh size are sub‐diffraction limited features and cannot be visualized effectively using confocal microscopy. In this work, we show that it is possible to image fluorenylmethoxycarbonyl‐protected diphenylalanine (FmocFF) hydrogels by points accumulation for imaging in nanoscale topography (PAINT) in native conditions and without direct gel labelling (see figure).